Analisis Kontingensi Sistem Tenaga Listrik dengan Metode Bounding - . Syafii; Nurul Rahmawati (Jurnal Rekayasa Elektrika, 2012)
The bounding method is one of the contingency analysis method for detecting branch flow violations. Three subnetworks in the bounding method namely N1, N2, and N3 will give information regarding those subnetworks that may not go overload and those that may. This research compared the results from contingency analysis that has been done to the 30 bus system using the bounding method and software PowerWorld Simulator 15 GSO. The result by using the bounding method is 12 lines can go overload for the outage of line 1-2. As well as for the outage of line 1-3 and the outage of line 2-5. Meanwhile, the output of using PowerWorld Simulator 15 GSO with DC power flow method, there are three overloads exist for the outage of line 1-2, three overloads exist for the outage of line 1-3, and five overloads exist for the outage of line 2-5. The overload lines are included in the group of lines that can overload from bounding result.